2019
DOI: 10.4490/algae.2019.34.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variations in macronutrient, amino acid, and fatty acid composition of mass-cultured Teleaulax amphioxeia (Cryptophyceae) strains

Abstract: To compare the nutritional quality of TPG (Teleaulax / Plagioselmis / Geminigera) clade species of cryptomonads with that of RHO (Rhodomonas / Rhinomonas / Storeatula) clade species 6 Teleaulax amphioxeia (TA) and 1 Rhinomonas sp. strains were mass-cultured in newly designed 500-L photobioreactors to the end of exponential growth phase. Intraspecific variations (IVs) in terms of one standard deviation among the 6 TA strains in the compositions of the three macronutrients were 41.5 (protein), 89.8 (lipid), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…Furthermore, controlling the pH of T. amphioxeia cultures may be not necessary as this species appears to tolerate pH from 6.0 (this study, data not shown) up to 9.4 (Smith and Hansen 2007). Thanks to the factorial design experiment, the present study determined the optimal conditions to obtain a large biomass that may be useful to exploit the beneficial role of T. amphioxeia as a food enrichment (Peltomaa et al 2018 andLee et al 2019). This approach also provided information on factors driving the bloom initiation of T. amphioxeia.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Furthermore, controlling the pH of T. amphioxeia cultures may be not necessary as this species appears to tolerate pH from 6.0 (this study, data not shown) up to 9.4 (Smith and Hansen 2007). Thanks to the factorial design experiment, the present study determined the optimal conditions to obtain a large biomass that may be useful to exploit the beneficial role of T. amphioxeia as a food enrichment (Peltomaa et al 2018 andLee et al 2019). This approach also provided information on factors driving the bloom initiation of T. amphioxeia.…”
Section: Discussionmentioning
confidence: 84%
“… and Lee et al. ). This approach also provided information on factors driving the bloom initiation of T. amphioxeia .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Further, cryptophyte cells can be broken and processed more easily than diatoms or dinoflagellates for commercial applications ( Scholz et al, 2014 ). Cryptophytes from the TPG ( Teleaulax / Plagioselmis / Geminigera ) and RHO ( Rhodomonas / Rhinomonas / Storeatula ) clades have been suggested as possible species for biotechnological purposes in the areas of health improvement, solar energy exploitation, and aquaculture ( Lee et al, 2019 ). The aim of this review is to summarize the promising microalgal compounds, with special emphasis on compounds derived from cryptophyte algae.…”
Section: Introductionmentioning
confidence: 99%